Doing diversity differently in a culturally complex world critical perspectives on multicultural education - Watkins, Megan; Noble, Greg (Bloomsbury Academic, 2021)
"Doing Diversity Differently in a Culturally Complex World explores the challenges facing multicultural education in the 21st century. The starting point is that the ideas fashioned in 1970s 'multiculturalism' are no longer adequate for the culturally complex world in which we now live. Much of what is provided in the name of multicultural education comes from a naïve perspective that avoids difficult questions around social relations, cultural flows and communal identities in today's globalised world. Megan Watkins and Greg Noble begin by exploring the understandings of multiculturalism that exist amongst teachers, parents and students. They demonstrate that ideas around identity and culture don't match the complexities of the social contexts of schooling in migrant-based nations such as Australia, the UK, the USA, Canada and New Zealand. Doing Diversity Differently in a Culturally Complex World draws on a comprehensive research project involving a large-scale survey of Australian teachers; interviews with teachers, parents and students and practitioner-led action research in 14 schools in Australia. The research involved primary and secondary schools from a range of contexts spanning urban and rural settings, high and low socio-economic status and high and low levels of cultural diversity. The book examines how schools address the problems around the diversity they face, considering how the strengths and limitations of each school's context reflects wider logics of traditional multiculturalism. In contrast, the authors argue for a transformative multiculturalism involving a more critically reflexive approach to understanding the processes, relations and identities of the contemporary world."
Includes bibliographical references and index
Keywords: Multicultural education / Australia; Multicultural education; Australia